Family‐Centered Practice in Adult Treatment Courts: What Can We Learn from the Family Treatment Court Best Practice Standards?. (12th April 2021) - Lloyd Sieger, Margaret H.; Cohen, Jeri B.; Nano, Xholina
Abstract: Estimates suggest that upwards of 50% of participants in adult treatment courts (ATC) are parents. Previous studies point to negative impacts of unmet parenting needs on substance use treatment and criminal justice outcomes, and that family‐centered practices such as parenting classes substantially reduce recidivism among ATC participants. Judges and team members interested in adopting family‐centered practices in their ATC program may be unsure where to begin. One recent source of information regarding evidence‐based, family‐centered practices in treatment court settings is the Family Treatment Court (FTC) Best Practice Standards. The FTC Standards suggest adopting a family‐centered mission, expanding partnerships with child‐ and family‐serving agencies, discussing parenting and family roles during hearings, implementing family‐centered case management, and considering the effect of therapeutic responses on children and families. Building on the ATC Standards, the flexibility inherent in voluntary court programs, and existing community partnerships creates a pathway toward family‐centered practice in criminal settings.